Does prospective control of preparatory heart rate responses occur during biathlon events? - Benum, S. D.; Van der Weel, F.; Sandbakk, O.; Van der Meer, A. (Complex Systems in Sport, International Congress 2017, 2017)
Biathlon is an Olympic winter sport that combines two essentially different sport skills, namely cross-country skiing in the skating technique and rifle shooting. A biathlon competition involves cross-country skiing, where the biathletes ski several 2-5 km laps in rolling terrain, interspersed with five shots of rifle shooting, alternating between the prone and standing position (International Biathlon Union, 2016). For each miss at the shooting range either 150 m of added skiing or a 1-min penalty is added to the final competition time. Successful biathlon performance thus depends on high aerobic power and well-developed skiing efficiency, as well as precise and rapid shooting abilities (Luchsinger et al., 2015). Biathletes usually ski at an intensity of 85-95% of maximum heart rate (HRmax) during competitions. However, a high heart rate accompanied by a high breathing frequency can be detrimental to shooting performance, since precise shooting requires the rifle to be held steady when aiming (Gallicchio et al., 2016). It might thus be beneficial for biathletes to regulate down their heart rate when approaching the shooting range. In addition, biathletes face diverse types of terrain, challenging them to regulate the metabolic intensity according to the demands of the terrain. Therefore, biathletes may prospectively increase their heart rate prior to, for example, a challenging uphill. The same type of heart rate regulation is expected to occur in connection with the start of a biathlon competition. Regulation of heart rate prior to the above events requires the biathlete to perceive what is going to happen in the near future so as to prepare the body accordingly, an ability that has been termed prospective control (Montagne, 2005; Lee, 2009). The aim of this study was to investigate preparatory heart rate patterns during simulated biathlon events to find evidence of prospective control. Prospective control was investigated in an ecologically valid field test, where electrocardiography (ECG) was continuously measured. The possible occurrence of prospective heart rate control was investigated in three central situations: (a) at the start, (b) when approaching uphill terrain during skiing, and (c) before shooting. We expected that biathletes would show prospective control in the form of an increase in heart rate prior to the start and the uphill terrain, and that a decrease in heart rate would occur prior to shooting.